Antioxidant and Cytotoxic Activities of Fractions of Ethanol Leaf Extract of Byrsocarpus Coccineus Schum. and Thonn. (Connaraceae) - Ukwade, Caroline E.; Ebuehi, Osaretin A. T.; Adisa, Rahmat A.; Odukoya, Abdulazeez; Agaba, Onyeka; Adesegun, Sunday A.; Igietseme, Joseph U.; Omosun, Yusuf (European Journal of Applied Sciences, 2022)
Medicinal plants have historically been used traditionally for their therapeutic potentials, they are therefore investigated with the hope of developing novel drugs. This study is to investigate the phytochemicals, antioxidant and cytotoxic activities of Byrsocarpus coccineus fractions. The ethanol leaf extract of B. coccineus was chromatographed on VLC over silica gel (Mesh 70-230) using n-hexane/EtOAc/MeOH eluent system; n-hexane/EtOAc (from100/0 to 0/100), then ethyl acetate (EtOAc)/MeOH (from 100/0 to 0/100) to yield seven (7) fractions.(F1-F7). The phytochemical screening and antioxidant activities of the different fractions were carried out. All the fractions were subjected to gas chromatography and mass spectrometry (GC-MS) analysis and cytotoxic activities of the different fractions were investigated using brine shrimp lethality assay. The phytochemical result showed that fractions contain tannins, flavonoids, phenols, reducing sugar, alkaloids, steroids, saponin and terpenoid. Antioxidant analysis show that F3 had the highest DPPH (IC50=56.88µg/ml) and NO (IC50=53.02µg/ml) free radical scavenging activities. F7 (IC50=56.25 µg/ml) and F3 (IC50 of 56.79 µg/ml), had the highest lipid peroxidation free radical scavenging activity. The brine shrimp toxicity assay result showed that F3 and F4 were cytotoxic to Artemia salina with a LD50 value of 39.01μg/ml and 53.55 μg/ml respectively. The GC-MS analysis showed the presence in the most active fraction with antioxidant (cis-vaccenic acid, neophytadiene), antitumor and cancer preventive (squalene) and anticancer (9-Octadecenoic acid, 9, 12-Octadecadienoic acid, methyl ester) potentials. This study reveals that B. Coccineus contains pharmacologically bioactive compounds with therapeutic potentials.